2021
DOI: 10.1042/bcj20210341
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of endo-glucanase 16 (EG16) activity across highly divergent plant lineages

Abstract: Plant cell walls are highly dynamic structures that are composed predominately of polysaccharides. As such, endogenous carbohydrate active-enzymes (CAZymes) are central to the synthesis and subsequent modification of plant cells during morphogenesis. The endo-glucanase 16 (EG16) members constitute a distinct group of plant CAZymes, angiosperm orthologs of which were recently shown to have dual beta-glucan/xyloglucan hydrolase activity.  Molecular phylogeny indicates that EG16 members comprise a sister clade wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Pp EG16 also exhibits significant activity on XyG (Behar et al, 2021), which has been reported in mosses (Roberts et al, 2012). Immunofluorescence of XyG using the LM15 antibody, which targets XXXG‐type non‐fucosylated XyGs (Marcus et al, 2008; Vincken et al, 1997), revealed wall‐specific labeling of wild‐type and ΔPpEG16‐1 protonema.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Pp EG16 also exhibits significant activity on XyG (Behar et al, 2021), which has been reported in mosses (Roberts et al, 2012). Immunofluorescence of XyG using the LM15 antibody, which targets XXXG‐type non‐fucosylated XyGs (Marcus et al, 2008; Vincken et al, 1997), revealed wall‐specific labeling of wild‐type and ΔPpEG16‐1 protonema.…”
Section: Resultsmentioning
confidence: 69%
“…Despite extensive biochemical and structural characterization that has defined polysaccharide specificity in divergent examples (Behar et al, 2021; Eklöf et al, 2013; McGregor et al, 2017), the biological function of EG16 orthologs is presently unknown. Since EG16 genes are strongly represented in non‐angiosperm genomes (Behar et al, 2018), we selected the moss P. patens as a well‐established model organism (Cove, 2005; Quatrano et al, 2007; Rensing et al, 2020) to explore the role of an exemplar EG16 in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In my view no plant enzyme has been documented to possess cell wall creep activity, even though many enzymes have at times been asserted to have such activity, for example, PME, pectinase, pectate lyase, xyloglucanase, cellulase, and others. Some bifunctional microbial endoglucanases (with xyloglucanase and cellulase activity) can induce plant cell wall creep ( Park and Cosgrove, 2012b ), but no plant equivalent has been discovered ( Behar et al, 2021 ). The results of Zhang et al (2019) showed that various wall lytic enzymes may soften cell walls (reduce their resistance to applied forces) yet not loosen the walls (not induce cell wall creep).…”
Section: Mechanisms Of Irreversible Wall Enlargementmentioning
confidence: 99%